I wonder why castles had moats and other questions about long ago - Steele, Philip, 1948-; local (New York : Kingfisher Books, 1994)
Who was Joan of Arc?
What were the Middle Ages in the middle of? -- Why did churches have steeples? -- Who wore platform shoes? -- Who was the first to chew gum? -- Why were books chained up? -- Why was it hard to tell time? -- Was Sinbad a real sailor? --
Includes index.
Questions and answers about castles, knights, and the times of long ago.
Follett Library Resources
Keywords: Follett Library Resources; sears -- Civilization, Medieval -- Miscellanea; Juvenile literature. -- Civilization, Medieval; Miscellanea. -- Medieval civilization; sears